2019
DOI: 10.1002/pat.4687
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic improvement of fire retardancy and mechanical properties of ferrocene‐based polymer in intumescent polypropylene composite

Abstract: The ferrocene-based polymer (PDPFDE) accompanied with traditional intumescent flame retardant (IFR) system (ammonium polyphosphate (APP)/pentaerythritol (PER) = 3/1, mass ratio) has been used as additive flame retardant in polypropylene (PP), aiming to lower the total loading amount. The thermal stability and fire retardant properties were investigated by thermogravimetric analysis (TGA), limiting oxygen index (LOI), vertical combustion (UL-94), and cone calorimetry (CONE). The fire retardant mechanism was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Whereas comparing with the calculated curve of APP and ZIF-67, the thermal decomposition started early and maximum weight loss rate of ZIF-67@APP at first decomposition step increased both N2 and O2 atmosphere. The phenomenon indicated that the ZIF-67 could accelerate the decomposition of APP and formation of the series structures of P-OH and Co 2+ -APP [52][53]. When the temperature increased from 450 °C to 700 °C under N2 atmosphere, the thermal decomposition step was divided into two steps and the maximum weight loss rate decreased obviously, and ZIF-67@APP displayed more residue up to 52.6 wt% from 27.9 wt% for APP at 700 °C, indicating that the synergistic effect existed between ZIF-67 and APP, which could promote the formation and the thermal stability of phosphorylation cross-linking structures at high temperature.…”
Section: Flame-retardant Mechanism Of Zif-67@app/epsmentioning
confidence: 98%
“…Whereas comparing with the calculated curve of APP and ZIF-67, the thermal decomposition started early and maximum weight loss rate of ZIF-67@APP at first decomposition step increased both N2 and O2 atmosphere. The phenomenon indicated that the ZIF-67 could accelerate the decomposition of APP and formation of the series structures of P-OH and Co 2+ -APP [52][53]. When the temperature increased from 450 °C to 700 °C under N2 atmosphere, the thermal decomposition step was divided into two steps and the maximum weight loss rate decreased obviously, and ZIF-67@APP displayed more residue up to 52.6 wt% from 27.9 wt% for APP at 700 °C, indicating that the synergistic effect existed between ZIF-67 and APP, which could promote the formation and the thermal stability of phosphorylation cross-linking structures at high temperature.…”
Section: Flame-retardant Mechanism Of Zif-67@app/epsmentioning
confidence: 98%
“…When IFR was added to PP0, the tensile and flexural strengths of PP1 were decreased by 8.7% and 5.7%, respectively, due to the partially poor compatibility, poor dispersion, and agglomeration of IFR in the polypropylene matrix. 36,[120][121][122] However, 2% MMT addition into PP1(PP/IFR) enhanced the mechanical properties. The tensile strength of PP2 became 41.3 MPa and the flexural strength increased to 54.7 MPa.…”
Section: Mechanical Properties Of Pp and Its Compositesmentioning
confidence: 99%
“…Therefore, in practical application, ferrocene is often used as a synergistic agent, and plays a synergistic effect together with other flame retardants. At present, studies have shown that there is a synergistic flame retardant and smoke suppression effect between ferrocene and halogen, 34 phosphorus, 35,36 nitrogen, 37 silicon 38 as well as intumescent 39 flame retardants.…”
Section: Introductionmentioning
confidence: 99%